Comparison of Green׳s function solutions for different heat conduction models in electronic nanostructures. Issue 12 (December 2015) - Janicki, Marcin; Samson, Agnieszka; Raszkowski, Tomasz; Zubert, Mariusz; Napieralski, Andrzej
Abstract: This paper compares Green׳s function solutions obtained for different heat conduction models, such as the Fourier–Kirchhoff heat equation, the Cataneo–Vernotte wave equation and the Dual-Phase-Lag equation. The solutions are computed for a nanometer size one-dimensional benchmark structure with Neumann and Dirichlet conditions imposed at its boundaries. Particular attention was paid to the analysis of heat diffusion speed predicted by the considered heat conduction models and its dependence on the time lag values.